On sourcing obsidian assemblages from the Mediterranean area: analytical strategies for their exhaustive geochemical characterisation. (April 2017) - Orange, Marie; Le Bourdonnec, François-Xavier; Bellot-Gurlet, Ludovic; Lugliè, Carlo; Dubernet, Stéphan; Bressy-Leandri, Céline; Scheffers, Anja; Joannes-Boyau, Renaud
Abstract: This paper presents an overview of the work conducted by our research group in the Mediterranean area. Initiated in the 1990s by the late Gérard Poupeau, our research relies on international and multidisciplinary collaborations to endeavour archaeological and anthropological issues linked to the diffusion and consumption of the obsidian raw material during the Neolithic period. Our line of action is to develop flexibly unique analytical strategies, tailored to each obsidian assemblage considered for a sourcing study. Drawing its strength from the complementarity of the methods available within our group, i.e. visual characterisation, SEM-EDS, ED-XRF, pXRF, PIXE, and LA-ICP-MS, this approach allows for the exhaustive and non-destructive analysis of those assemblages, thus optimising the potential of sourcing studies. Working hand in hand with archaeologists, the results are closely integrated to the information brought by the typological and technological characteristics of the artefacts, in the aim to reconstruct an overview of the obsidian economy at site level, but also to replace it in a broader — regional and supra-regional — context. Highlights: Non-destructive and exhaustive analyses of lithic assemblages are recommended The concept of analytical strategy for obsidian sourcing studies is introduced. Integration of sourcing results with typo-technological data is imperative. The importance of international multidisciplinary collaborations is highlighted.